Thermal evaluation of a double glazing façade system with integrated Parallel Slat Transparent Insulation Material (PS-TIM) - Sun, Yanyi; Wu, Yupeng; Wilson, Robin; Sun, Shuyue (Elsevier, 2016)
Concerns over sustainability in the built environment have resulted in continuous efforts to improve the performance of glazed façade systems and hence indoor comfort and building energy conservation. An innovative façade system where parallel transparent plastic slats are sandwiched between glass panes to form a Parallel Slat Transparent Insulation Material (PS-TIM) is proposed as a strategy to effectively reduce coupled convective and radiative heat transfer between the panes of a double glazed window. This strategy increases the thermal resistance of the façade, while maintaining access to daylight. A numerical investigation of the thermal and optical performance of this façade system is presented. Detailed modelling of the thermal characteristics of a double glazed window containing PS-TIM systems was carried out for different cell aspect ratios (defined by the thickness of window air cavity and slat interval distance), slat thickness and slat properties (conductivities and emissivities) using a validated Computational Fluid Dynamic (CFD) model. The CFD predictions show that: 1) an aspect ratio of 0.35 can provide full suppression of convection; 2) the PS-TIM structure can achieve a 35–46% reduction in thermal conductance compared with the same double glazing in the absence of PS-TIM; 3) material conductivity, thickness and emissivity have a more apparent influence on small cell structures than large cell structures. In addition, a simple analysis of U-value and light transmittance at various solar incidence angles was undertaken. The results provide a better understanding of the benefits of PS-TIM in terms of energy saving and offer suggestions for the improved design of glazing façade systems.